2002
DOI: 10.5014/ajot.56.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Handwriting and Keyboarding Performance of Sixth-Grade Students

Abstract: Keyboarding performance demonstrated low to moderate correlation with handwriting performance, suggesting that these forms of written expression require distinctly different skills. Most students who were slow at handwriting or had poor legibility increased the quantity and overall legibility of text they produced with a keyboard. These results suggest that keyboarding has the potential to increase and improve a student's written output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 19 publications
5
43
1
3
Order By: Relevance
“…Des recherches menées par Bui, Myerson et Hale (2013) sur la prise de notes électronique relèvent la présence des mêmes processus cognitifs d'encodage et de stockage que pour les notes manuscrites. Bui et al (2013) ainsi que Rogers et Case-Smith (2002) se sont attardés à la prise de notes avec un clavier et soutiennent que la vitesse de frappe n'est plus un élément significatif dans la performance des étudiants. Le plus important serait plutôt la préparation et la formation de ces derniers à utiliser des stratégies efficaces pour favoriser l'apprentissage (Yang & Chiu, 2014).…”
Section: La Prise De Notes Avec Une Tablette Numériqueunclassified
“…Des recherches menées par Bui, Myerson et Hale (2013) sur la prise de notes électronique relèvent la présence des mêmes processus cognitifs d'encodage et de stockage que pour les notes manuscrites. Bui et al (2013) ainsi que Rogers et Case-Smith (2002) se sont attardés à la prise de notes avec un clavier et soutiennent que la vitesse de frappe n'est plus un élément significatif dans la performance des étudiants. Le plus important serait plutôt la préparation et la formation de ces derniers à utiliser des stratégies efficaces pour favoriser l'apprentissage (Yang & Chiu, 2014).…”
Section: La Prise De Notes Avec Une Tablette Numériqueunclassified
“…Previous research on handwriting difficulties among children with motor disabilities, including children with AS, has often been based on observations and has focused on motor function (2,4,5,12,13,14). So far evidence that kinesthetic or sensory motor based training substantially improves handwriting is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in which typically children participated they found that keyboarding and handwriting might require different skills of the child, which shows that use of a computer could be an alternative writing method for schoolchildren with handwriting difficulties. Rogers and Case-Smith (12) found that handwriting speed and legibility among typically developing students showed low to moderate relationships with keyboarding speed. They keyboarded faster than they wrote by hand and most participants who wrote slowly by hand and those with poor legibility increased quantity and legibility when they keyboarded (12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations